Profil beban kognitif siswa SMA selama masa pandemi covid-19 - Muhammad Irfan Rumasoreng (AKSIOMA : Jurnal Matematika dan Pendidikan Matematika, 2021)
Students' cognitive load is the biggest threat in the learning process, the purpose of this study is to analyze the cognitive load profile of high school students during the Covid-19 pandemic, the sample in this study were 138 high school students, the instrument used was a questionnaire, the research method was descriptive quantitative. Quantitative data were analyzed using lisrel 8.5. The results showed that (1) students experienced a cognitive load of 83%, (2) The sub-dimension of cognitive load that had the greatest contribution was intrinsic, (3) The intrinsic sub-indicator that caused the student's cognitive load was in the question of the material being taught.